Bupivacaína 0,25% peridural, en la analgesia de parto; efectos hemodinámicos en la madre y feto - Arias, Silvia (2006)
Objectives: To determine peridural bupivacaine analgesia for labor pain relief and its effect on maternal and fetal hemodynamics. Design: Prospective, longitudinal, descriptive study. Setting: Obstetrical Center, Maternal and Perinatal Specialized Institute, Lima, Peru, a teaching hospital. Patients: Sixty patients in active phase of labor. Interventions: Twelve mL of 0,25% bupivacaine was given to the women in labor through epidural catheter. Visual analog scale was used to evaluate pain during labor. Maternal and fetal hemodynamic changes were described before and following epidural analgesia. Supplementary dosis of 6 mL 0,25% bupivacaine was used. Cardiotocographic tracings were registered and maternal and fetal complications were determined. Main outcome measures: Labor pain relief, maternal hemodynamics, fetal pH. Results: There was statistically significant pain relief using 12 mL of 0,25% bupivacaine (p < 0,001). Supplementary dosis of bupivacaine was needed in 33 patients (X: 45 mg). Baseline fetal heart rate before and after epidural analgesia was 142 beats/ min and 136 beats/min, respectively (p < 0,05). Analgesic blockade reached T8; 115 minutes was the analgesia median time. Patient satisfaction was excellent in 50,1%. Oxytocin was used in 88,3% patients (13,3 mIU/min ± 3,2 mIU/min). Active phase labor length was shortened by 2,42 hours in primiparous and 1,55 hours in multiparous. Cesarean deliveries were peformed in 11,7%. Mean neonatal pH was 7,24. Conclusions: Epidural analgesia with bupivacaine 0,25% via catheter results in effective labor pain relief. Fetal heart beat decreased 12 beats/min. Phase active was shortened since oxytocin was used during this period.